Kinematic analysis of the snatch technique used by Japanese and international female weightlifters at the 2006 Junior World Championship - Okada, J.; Iijima, K.; Fukunaga, T.; Kikuchi, T.; Kato, K. (International Journal of Sport & Health Science, 2008)
The purpose of the present study was to compare the snatch techniques of Japanese and international female weightlifters using kinematic analysis. Motion analysis of the snatch techniques conducted using videos recorded at the 2006 Women's Junior World Weightlifting Championship. The results indicated no significant differences between the snatch techniques of Japanese and international weightlifters in terms of the kinematic parameters expressed by the barbell trajectory and joint angles. However, the interval of time between the peak velocity of the hip joint and peak vertical velocity of the barbell was longer for Japanese weightlifters, while the power applied to the barbell was 35% greater for international weightlifters. These findings indicate that differences in strength and power production affected the performances of Japanese and international weightlifters.